Computational identification of hepatitis E virus‐encoded microRNAs and their targets in human. Issue 8 (9th April 2019) - Baruah, Vargab; Bose, Sujoy
Abstract: microRNAs (miRNAs) are small, noncoding RNAs which regulate eukaryotic gene expression via RNA interference pathway. Recently, miRNAs have been identified in a number of viruses with current evidence suggesting that they regulate gene expression in both virus and host. This makes viral miRNAs potential targets of clinical intervention, with the possibility of inhibiting aberrant host gene expression associated with the disease. In this study, computational approaches were taken to scan the hepatitis E virus (HEV) genome for putative pre‐miRNA molecules, which were then analyzed for the presence of mature miRNAs. The 3′‐untranslated region (3′‐UTR) and 5′‐UTR sequences targeted by these miRNAs were identified using Miranda computational tool, followed by the functional annotation of the associated messenger RNAs (mRNAs) using Gene Ontology terms and Kyoto Encyclopaedia of Genes and Genomes pathway analysis. We identified a total of nine viral encoded miRNAs in HEV. After functional annotation, the majority of the viral miRNA targets were found to be associated with cell cycle, cell differentiation, nitrogen compound metabolism, transmembrane transport, and chromosome organization. This in‐silico study identified putative viral miRNAs encoded by HEV and their potential human mRNAs targets. These viral miRNAs have the potential to affect host gene expression as well as viral life cycle and pathogenesis and can, therefore, serve as potential therapeutic targets during HEV infection. Highlight: We computationally analyzed the Hepatitis E Virus genome for putative miRNAs. Nine virus encoded miRNAs were detected. The human UTR targets of these miRNAs were identified and functionally annotated. These viral miRNAs could be potential therapeutic targets.